Assessment of Quality of life for Patients with Myocardial Infarction - Yass K. Abbas, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To identify quality of life (QOL) in Myocardial Infarction (MI) patients, and to find out therelationship between QOL in MI patients and demographic characteristics.Methodology: A descriptive colTelation study which utilized an assessment approach. The study was carried outfrom March 2007 through November 2007 in order to assess the quality of life for patients with myocardialinfarction. A purposive "non-probability" sample of (75) patients with myocardial infarction who were attendingto Baquba General Hospita`l through their visits to that hospital. A questionnaire was adapted and developedfrom the World Health Organization Quality of Life Scale (1998). The questionnaire was designed andconsisted of (2) parts, the fust part includes demographic characteristics of Myocardial Infarction patients,clinical characteristics of these patients and medical sheet information. The second one consists of six domainsof quality of life. Reliability was determined by using test and retest technique through a Pilot study. Data wereanalyzed through descriptive data analysis approach (Frequency and percentage) and the inferential data analysisapproach (Pearson con.elation coefficient and chi-square).Results: The results of the study indicated that (53.3%) of the sample was male and (41.7%), age between (61-70) years, (68.0%) was married and more than two third of sample were unable to read and write, (44%) of thesample was housewife (do not work). The findings of the study present that the demographic characteristics ofMI patients such as gender, level of education had a significant relationship with their quality of life. Thesocioeconomjc characteristics of patients such as marital status hnd no significant relationship with the patients'quality of life. The finding also shows disease had moderate, low and no effect on quality of life through therelative sufficiency from the spiritual domain (RS=83.8), the independence (RS=76.9), psychological domain(RS=76.7), physical domain (RS=74.6), social domain a`S=69.9), and environment domain (RS=62.3).Recommendations: The study recommended that an educational program for MI patients to help them have abetter QOL and advice them how to cope with their problems for a good QOL.